Influence of Tamarind Pulp on Growth Performance, Carcass Characteristics and Relative Weights of Internal Organs of Japanese quail Raised in Hot Climates (Indian Journal of Animal Production and Management, 2026)
This study aimed to evaluate the influence of an aqueous extract of tamarind  pulp on production performance, carcass characteristics, and internal organ  traits of Japanese quail raised under hot climatic conditions. In a completely  randomized design, 160 one-day-old quail chicks were allocated to 4  groups (treatments) with 4 replicates each (10 birds per cage). The control  group (T1) received no tamarind extract, while the experimental groups  (T2, T3, and T4) were supplied with 5, 15, and 25 grams of tamarind pulp  per liter of drinking water, respectively, starting from age 4 up to 42 days  old, for 12 hoursevery day. The results of this study showed that adding  tamarindin different proportions, compared to the control treatment, led  to significantly increased (P < 0.05) feed intake for T3 and T4 treatments. The highest significant improvements (P < 0.05) in live body weight and  weight gain were recorded in the T3 treatment. No significant differences  (P < 0.05) were observed among treatments in feed conversion ratio and  mortality rate. Carcass weight was significantly higher (P < 0.05) in the T3  treatment. The relative weight of the thighs increased significantly (P < 0.05)  in the T2 treatment, while in the same treatment, a significant reduction (P  < 0.05) was recorded in the weight of the relative wing. The weight of the  liver relative was significantly higher (P < 0.05) in the T4 treatment. Both the  relative weight of the gizzard and abdominal fat were significantly increased  (P < 0.05) in the T3 treatment. In summary, supplementing drinking water  with 5, 15, and 25 g/L of tamarind pulp during hot climatic conditions did  not adversely affect performance or carcass traits of Japanese quail; rather, it  enhanced several productive and physiological parameters. Overall, the 15  g/L level (T3) was identified as the most effective treatment.
Keywords: Japanese Quails; Tamarind Pulp; Influence; Growth Performance; Hot Climates